2020
DOI: 10.1371/journal.pone.0233261
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl hydroxylase domain 2 reduction enhances skeletal muscle tissue regeneration after soft tissue trauma in mice

Abstract: The transcription factor Hypoxia-inducible factor 1 (HIF-1) plays a pivotal role in tissue regeneration. HIF-1 is negatively controlled by O 2-dependent prolyl hydroxylases with a predominant role of prolyl hydroxylase 2 isoform (Phd2). Transgenic mice, hypomorphic for this isoform, accumulate more HIF-1 under normoxic conditions. Using these mice, we investigated the influence of Phd2 and HIF-1 on the regenerative capability of skeletal muscle tissue after myotrauma. Phd2-hypomorphic and wild type mice (on C5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 65 publications
(95 reference statements)
0
9
0
Order By: Relevance
“…For instance, previous studies have shown that PHD2 can regulate skeletal muscle fiber type transition and inhibit skeletal muscle regeneration through the calcineurin / NFATc1-dependent pathway. [33][34][35] In addition, mice with the interference of PHD1 or PHD3 activity also had a protective effect on hind limb ischemia and reduced muscle mass loss after ischemic injury. 36,67 Similarly, salidroside, a drug inhibitor, inhibited PHD3, and restored the proliferation and angiogenic factor secretion potential of skeletal muscle cells inhibited by hyperglycemia.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, previous studies have shown that PHD2 can regulate skeletal muscle fiber type transition and inhibit skeletal muscle regeneration through the calcineurin / NFATc1-dependent pathway. [33][34][35] In addition, mice with the interference of PHD1 or PHD3 activity also had a protective effect on hind limb ischemia and reduced muscle mass loss after ischemic injury. 36,67 Similarly, salidroside, a drug inhibitor, inhibited PHD3, and restored the proliferation and angiogenic factor secretion potential of skeletal muscle cells inhibited by hyperglycemia.…”
Section: Discussionmentioning
confidence: 95%
“…PHD2 suppression in skeletal muscle cells has been shown to enhance HIF-1α accumulation and angiogenic factors’ expression ( Wu et al., 2015 ; Settelmeier et al., 2020 ). As the downstream factors of HIF-1α, VEGF-A and PDGF-BB could exert an autocrine signaling to stimulate skeletal muscle cells’ proliferation and migration potentials ( Webb and Lee, 1997 ; Germani et al., 2003 ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study in vivo showed that Phd2-deficency and the subsequent Hif-1α accumulation in mice enhanced and accelerated skeletal muscle regeneration after a myotrauma [100]. In this model, the authors also described an accelerated macrophage recruitment to the injured area [100]. Myotrauma was also reported to induce a hypoxic microenvironment leading to Hif-1α accumulation in myofibers and myeloid cells.…”
Section: Impact On Myogenesis and Regenerationmentioning
confidence: 96%
“…In normoxic conditions, Hif-1α can be detected in skeletal muscle but its protein level is dependent on the muscle fiber type [104]. A recent study in vivo showed that Phd2deficency and the subsequent Hif-1α accumulation in mice enhanced and accelerated skeletal muscle regeneration after a myotrauma [100]. In this model, the authors also described an accelerated macrophage recruitment to the injured area [100].…”
Section: Impact On Myogenesis and Regenerationmentioning
confidence: 97%
See 1 more Smart Citation